Analisis dan Desain SiBIOS: Deteksi Dini Kondisi Jantung dan Peningkatan Kualitas Hidup Manusia - Rahmawati Febrifyaning Tias; Muhammad Mahaputra Hidayat (Techno.Com, 2018)
One indicator of the quality of human life is the heart condition. So it is very important for every individual to know whether his heart is in good condition or not. One way to use is to analyze heart rate. Through Self Integrated Bio-Informatics System - SiBIOS, each individual will be able to detect early presence or absence of cardiovascular disorders. SiBIOS is a mobile app associated with smartwatch tools to measure heart rate. In order for SiBIOS to be properly and purposefully developed, the analysis and design stages are one of the most important stages in the development of SiBIOS. Through this stage we get a picture of SiBIOS that will be developed. In addition to providing primary outcomes in the form of early detection of heart conditions, SiBIOS also provides additional outcomes in the form of calorie burning charts, activity chart and individual sleep quality chart. SiBIOS also provides recommendations of activities that can be done by individuals to keep their heart condition in order to remain prime